Public Speaking Enhancement Workshop For Children of Migrant Workers In Penang Malaysia - Afdal Makkuraga Putra; Eka Perwitasar; Heri Budianto; Mardhiyyah Mardhiyyah (International Journal Of Community Service, 2025)
Public speaking is an essential skill in the era of globalization that enhances self-confidence, academic competence, and career opportunities. However, Indonesian migrant workers' children in Penang, Malaysia, face challenges in developing this skill due to a lack of training, limited access to communication education, and fear of speaking in public. Therefore, the Public Speaking Enhancement Workshop for Children of Migrant Workers in Penang, Malaysia is designed to equip participants with effective speaking skills through the Participative Active Learning (PAL) method. This two-day workshop, scheduled for May 4-5, 2025, will employ an interactive approach that includes speech exercises, simulations, and social media-based evaluations. The training have covered voice modulation techniques, speech style selection, and topic development. The POBC (Planning, Opening, Body, Conclusion) method were applied to help participants structure their presentations persuasively. Additionally, the evaluation process have involved monitoring participants' social media activities and assessing their short speech videos. This program supports higher education institutions' key performance indicators (IKU), particularly regarding lecturers' engagement outside the campus. The program’s sustainability will be ensured through post-workshop monitoring and collaboration with the local community. Expected outcomes include publications in national and international journals and the improvement of participants' communication skills in professional settings. With a systematic and participatory approach, this workshop is expected to create a lasting positive impact on migrant workers' children by enhancing their public speaking skills and preparing them for future challenges.